Self-Organized Parallel Processing System - HAMAOKA YOSHIYUKI; ISHIBASHI KAZUKO; HAYASHI HIROO (2009)
Systems and methods for improving the performance of a multimedia processor system by dynamically evaluating the current performance of the system and, if necessary, updating the configurations of the individual processors to improve the performance of the system. One embodiment comprises a method implemented in a multiprocessor system, including evaluating the performance of each of a current set of configuration objects installed on the processors, selecting a preferred set of configuration objects, and replacing one or more of the configuration objects in the current set to conform the current set to the preferred set. The method may evaluate the performance of each configuration object according to user preferences and may select preferred configuration objects according to a selectable strategy that can, for example, favor unification or diversity in the types of preferred configuration objects.